Informal Colombia : a general equilibrium analysis of the colombian labour market (2019)
This paper studies a general equilibrium model of real cycles calibrated for the Colombian labour market. The model is based in Shimer's (2010) extended to include a dual market where formal workers and informal workers coexist. I calibrate this model with the available Colombian data in order to replicate the cyclical behaviour of this labour market.